Dense yet highly ion permeable graphene electrodes obtained by capillary-drying of a holey graphene oxide assembly. Issue 20 (8th May 2019) - Chen, Xiangrong; Han, Junwei; Lv, Xiaohui; Lv, Wei; Pan, Zhengze; Luo, Chong; Zhang, Siwei; Lin, Qiaowei; Kang, Feiyu; Yang, Quan-Hong
Abstract : The density and ion channel abundancy of an electrode material must be elaborately balanced to achieve a high volumetric energy density for any energy storage devices. Abstract : The density and ion channel abundancy of an electrode material must be elaborately balanced to achieve a high volumetric energy density for any energy storage devices. As a typical example, graphene shows great potential in different energy storage devices but its low density and ion diffusion barrier effect limit its practical uses. In the present work, H2 O2 etching was introduced into the hydrothermal assembly of graphene oxide (GO) to decrease the lateral size of GO and create in-plane holes, and after a capillary drying process, a high-density holey graphene monolith (HHGM) with numerous and interconnected ion transporting channels was obtained. The smaller sheet size leads to a more densified assembly while in-plane holes are beneficial to ion transportation in the HHGM, which well balance the high density and fast ion diffusion in the electrode. As a result, the HHGM shows an impressive rate performance, coupled with a high volumetric capacitance.